Addressing the National Crisis Facing Black and Latina Women, Birthing People, and Infants: The Maternal and Child Health Equity Summit. Issue 3 (2nd March 2023) - Krishnamoorthi, Mahima; Balbierz, Amy; Laraque-Arena, Danielle; Howell, Elizabeth A.
Abstract : The Maternal and Child Health Equity Summit framed the national crisis of maternal and infant health disparities and produced recommendations to inform hospital and policy changes. Abstract : To address the national crisis of maternal and infant health disparities, especially outcomes experienced by Black and Latina women and birthing people, The New York Academy of Medicine, the Icahn School of Medicine at Mount Sinai, the Blavatnik Family Women's Health Research Institute, and the University of Pennsylvania Health System and Perelman School of Medicine hosted the Maternal and Child Health Equity Summit. The primary purpose of the summit was to disseminate findings to a national audience of two National Institutes of Health–funded mixed-methods studies that investigated the contribution of hospital quality to disparities in maternal and infant Health in New York City (R01MD007651 and R01HD078565). In addition, the summit showcased factors in maternal and infant health inequity from leading diverse experts in both fields and identified outstanding challenges to reducing maternal and infant morbidity and mortality disparities and strategies to address them. Summit presenters and participants identified five primary areas of focus in proposed clinical actions and approaches for maternal and neonatal health care based on discussions during the summit: 1) quality and standardization of care; 2) adjustment of care strategy based on patient-reported experience; 3) health care professional and institutional accountability to patients; 4) commitment to building trust; and 5) anti-racism practices in education, training, and hiring. Recommendations from this conference should inform hospital care and public policy changes and frame a national agenda to address perinatal health disparities for Black, Indigenous, and other women and birthing people of color.